ZAKAT INSTITUTION UNDER THE GOVERNMENT: POLITICAL INTEREST, CHARITY AND RESISTANCE - Huda, Yasrul (El-Qist: Journal of Islamic Economics and Business (JIEB), 2012)
This article investigates an involvement of the government of the Municipaltiy of Padang in West Sumatra in managing zakat institution, namely BAZDA (Badan Amil Zakat Daerah). It argues that the intentions of the mayor in managing the zakat institution aimed to provide an alternative financial source in order to support his position at the mayor. Zakat payers (Muzakki), collector (Ê¿amil), kinds of property obligated to pay its zakat (mÄl) and recipients (mustaá¸¥iq) are mainly the matters that link to his authority. The zakat revenue initially was mainly distributed to recipients in form of charity, but since 2010 it has gradually shifted to financialize busninesse run by the poor and needy. The mayor received resistances from many people, but they are mainly in form of individual resistance that are lacking to force the mayor to change his policy. In addition, the emerging resistance is rooted in different values between the mayor and resisters.